Implementation of an Automated High-Throughput Plasmid DNA Production Pipeline. (December 2016) - Billeci, Karen; Suh, Christopher; Di Ioia, Tina; Singh, Lovejit; Abraham, Ryan; Baldwin, Anne; Monteclaro, Stephen
Biologics sample management facilities are often responsible for a diversity of large-molecule reagent types, such as DNA, RNAi, and protein libraries. Historically, the management of large molecules was dispersed into multiple laboratories. As methodologies to support pathway discovery, antibody discovery, and protein production have become high throughput, the implementation of automation and centralized inventory management tools has become important. To this end, to improve sample tracking, throughput, and accuracy, we have implemented a module-based automation system integrated into inventory management software using multiple platforms (Hamilton, Hudson, Dynamic Devices, and Brooks). Here we describe the implementation of these systems with a focus on high-throughput plasmid DNA production management.